Hypersulfate-excited low-carbon cementing material based on alkali-containing solid waste as raw material and preparation method of hypersulfate-excited low-carbon cementing material

Through the combination of thermal activation process and ethylenediamine ion chelating agent, the alkalinity in the hydration and hardening of red mud is regulated, and the problems of low activity and high alkalinity of red mud are solved, and the mechanical properties of red mud-sulphate cement are improved. , achieving efficient utilization of red mud resources and alleviating the shortage of mineral powder.

CN119241151AActive Publication Date: 2025-01-03UNIV OF JINAN

Patent Information

Application Number
CN202411399096.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The problems of low activity and high alkalinity of red mud in the prior art have led to early strength development obstacles in the hydration and hardening of red mud-ultrasulfate cement, and they are too dependent on high-quality mineral powder, making it difficult to effectively utilize red mud resources.

Method used

Calcium sulfosilicate with solid alkali characteristics was prepared by thermal activation process, and combined with ethylenediamine ion chelating agent, the alkalinity during the hydration of red mud was regulated, and a supersulfate-energized low-carbon glue based on alkali-containing solid waste was designed. The cementitious material and its preparation method include red mud precursor gelling material, solid waste material, alkali excitant and sulfate excitant, and combined with composite additives to improve the mechanical properties of the gelling material.

Benefits of technology

It realizes efficient activity excitation of red mud, regulates alkalinity during hydration and hardening, improves the early compressive strength and later mechanical properties of gelled materials, reduces the firing temperature of calcium sulfosilicate, and reduces energy consumption and Carbon emissions have promoted the resource utilization of red mud and solved the problems of mineral powder shortage and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241151A_ABST
    Figure CN119241151A_ABST
Patent Text Reader

Abstract

The invention discloses a super-sulfate-activated low-carbon cementing material based on alkali-containing solid waste as a raw material and a preparation method thereof. The cementing material comprises the following raw material components in percentage by mass: 30-50% of a red mud precursor cementing material, 34-54% of a solid waste material, 0.5-2% of an alkali activator and 10-20% of a sulfate activator. The application range of a sulfate excited low-carbon cementing material system is expanded, efficient utilization of the red mud can be achieved, alkaline solid waste such as the red mud becomes necessary components, and the problem of shortage of high-quality auxiliary cementing materials and the environmental problem caused by stacking of the red mud can be solved at the same time; the thermally activated red mud in the formula not only provides high-activity aluminum-silicon potential for performance development of the cementing material, but also provides proper alkalinity to make up for strength reduction caused by insufficient alkali in the later stage of the system, and promotes improvement of mechanical strength of the cementing material and densification of a matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as a raw material and a preparation method thereof. Background Art

[0002] Red mud is a highly alkaline solid waste produced during the Bayer process of producing alumina. It has a huge emission volume and a very low utilization rate. The treatment method based on damming and stockpiling not only occupies a large amount of land resources, but also has major safety hazards such as alkaline filtrate alkalizing the soil and contaminating groundwater.

[0003] Partial replacement of cement clinker with aluminosilicate solid waste is a common resource utilization method. For red mud, people often use the aluminum-rich siliceous components in red mud to prepare silicate cement clinker and sulphoaluminate cement clinker; use the high iron content (about 40-60wt.%) in red mud to prepare high-iron ore phase raw materials or use it as an active stimulating component of low-activity aluminosilicate solid waste. Therefore, red mud has the potential to be used as an auxiliary cementitious material for cement.

[0004] Super sulfated cement (SSC) is a low-clinker cement with granulated blast furnace slag as the main raw material, gypsum as the sulfate activator, and clinker or lime as the alkaline activator. Its component ratio is usually 75% to 85% slag, 10% to 20% sulfates (such as dihydrate gypsum, anhydrous gypsum, phosphogypsum, etc.) and 1% to 5% alkaline components (such as clinker, calcium hydroxide, lime, etc.). The energy consumption and CO2 emissions during the preparation of super sulfated cement are extremely low, and it is a typical low-energy and low-carbon cement. However, high-quality mineral powder is widely used as an auxiliary cementitious material in the cement industry, resulting in a shortage of supply. Therefore, activating the highly active aluminum-silica components in red mud and making them replace the mineral powder in SSC in large quantities to prepare red mud-super sulfated cement (RM-SSC) can effectively solve the problem of shortage of high-quality mineral powder in the production process of SSC.

[0005] The use of thermal activation technology can effectively stimulate the activity of aluminum-silica components in red mud. The optimal thermal activation temperature of red mud is 900°C, at which time the amount of active aluminum dissolved in the red mud is the largest, with the highest activity (66.38%). However, while satisfying the high activity of red mud, the high alkalinity characteristics of red mud (mainly Na2O, about 5-13wt.%, alkali is easily dissolved after cement hardening, hindering the long-term strength development of cement) will hinder the formation and growth of calcium sulfonite and CSH gel in the hydration products of SSC and restrict the early and late strength development. Therefore, the rational regulation of the alkalinity of SSC is the key to the preparation of RM-SSC.

[0006] Alkali metal ions (Na + ) is dissolved in calcium sulfosilicate (C 5-x Na xS2$) crystal structure. During the red mud calcination process, calcium carbonate (CaCO3, component ratio is 16.50-33.00wt.%) and gypsum (CaSO4·2H2O, component ratio is 7.15-14.30wt.%) are added to burn the red mud precursor cementitious material containing 5-10wt.% calcium sulfosilicate (C5S2$). + Solid solution properties, regulating the alkalinity during red mud hydration, can stabilize the early mechanical strength development of RM-SSC. In addition, C5S2$ is a mineral phase with a certain late hydration potential in an aluminum-containing liquid environment. + Slow and continuous dissolution in the late stage of hydration regulates the alkalinity of RM-SSC in the late stage of hydration, continuously stimulates the hydrolysis of unreacted red mud and mineral powder, and provides the necessary environment for the development of mechanical strength in the later stage.

[0007] Chelating agents are a class of compounds that can form complexes with metal ions. The mechanism of action is that metal ions react with ligands containing two or more coordinating atoms to form complexes with ring structures. They are currently commonly used in agriculture, medicine, food and other fields. Studies have shown that chelating agents are also suitable for the construction field to complex heavy metal ions in cement concrete. Disodium ethylenediaminetetraacetic acid is a typical sodium ion chelating agent that can be used to adsorb sodium ions in a complexing environment. Studies have shown that ethylenediamine compounds react with functional groups such as aldehydes and sulfonic acid groups to form intermediates with imine structures. Through redox reactions, they are converted into ethylenediamine derivatives containing carbonyl groups, which can further improve the chelating ability of ethylenediamine with sodium ions. Therefore, the application of chelating agents in red mud-supersulfated cement is expected to reduce the influence of excessive alkali in red mud on the increase of environmental pH and thus affect the early hydration rate of cementitious materials, thereby improving the early compressive strength.

[0008] Therefore, it is necessary to provide a reliable solution for using red mud and aluminosilicate solid waste to prepare cementitious materials to achieve their resource utilization. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material and a preparation method thereof in view of the deficiencies in the above-mentioned prior art. The present invention aims at the problem of low red mud activity and high alkalinity in the preparation process of cement cementitious materials prepared by dealkalization of traditional high-alkali solid waste. The present invention uses a thermal activation process to make red mud obtain a certain activity and burns calcium sulfosilicate with solid alkali characteristics in this process, so as to achieve the goal of regulating the alkalinity in the hydration and hardening process of RM-SSC (red mud-supersulfate cement). A new supersulfate-activated low-carbon cementitious material prepared by alkali-containing solid waste and a preparation method thereof are designed to solve the problem of rational application of red mud resources and reduce excessive dependence on high-quality mineral powder in the production process of supersulfate cement.

[0010] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: in the first aspect of the present invention, a super sulfate activated low-carbon cementitious material based on alkali-containing solid waste as raw material is provided, comprising the following raw material components by mass percentage: 30-50% of red mud precursor cementitious material, 34-54% of solid waste material, 0.5-2% of alkali activator, and 10-20% of sulfate activator.

[0011] Preferably, the preparation method of the red mud precursor gelling material is: mixing red mud, calcium carbonate and dihydrate gypsum, calcining at 950-1050° C. for 1-4 hours, and cooling to obtain the red mud precursor gelling material.

[0012] Preferably, the mass ratio of red mud:calcium carbonate:dihydrate gypsum is 6.9-13.9:2.3:1.

[0013] Preferably, the preparation method of the red mud precursor gelling material is:

[0014] The red mud was dried at 105° C. for 48 hours, ground by a ball mill for 45 minutes, passed through an 80-mesh sieve, and then mixed evenly with calcium carbonate and dihydrate gypsum, heated to 1000° C. at a heating rate of 5° C. / min, calcined for 2 hours, and taken out to cool in air to obtain the red mud precursor gelling material;

[0015] Among them, the mass ratio of red mud: calcium carbonate: dihydrate gypsum is 13.9:2.3:1.

[0016] Preferably, the solid waste material is blast furnace powder, the alkali activator is at least one of silicate cement, clinker, and calcium hydroxide, and the sulfate activator is at least one of hard gypsum, anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, and phosphogypsum.

[0017] Preferably, the raw material components of the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material also include a composite additive with a weight percentage of 0.5-2%, and the composite additive is a mixture of a concrete early strength agent, a polycarboxylate water reducer, and an ion chelating agent;

[0018] Among them, the mass ratio of concrete early strength agent: polycarboxylate water reducer: ion chelating agent is 4:1:2;

[0019] Wherein, the concrete early strength agent is triethanolamine, and the ion chelating agent is ethylenediamine ion chelating agent.

[0020] Preferably, the raw material components of the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material further include a composite additive with a mass proportion of 0.5-2%, wherein the composite additive is a mixture of a polycarboxylate water reducer and a modified ethylenediamine ion chelating agent, and the mass ratio of the polycarboxylate water reducer to the modified ethylenediamine ion chelating agent is 1:2;

[0021] Wherein, the modified ethylenediamine ion chelating agent is prepared by the following method:

[0022] Add 100-400g of ethylenediamine to a four-necked flask, add 7.5-30g of formaldehyde dropwise at 0°C with continuous stirring, and simultaneously add triethanolamine dropwise during the process to keep the pH of the reaction solution not less than 11. The addition time is 0.5-2h, and then react at 30-50°C for 1.5-6h to obtain a modified ethylenediamine ion chelating agent.

[0023] Preferably, the modified ethylenediamine ion chelating agent is prepared by the following method:

[0024] 200 g of ethylenediamine was added to a four-necked flask, and 15 g of formaldehyde was added dropwise at 0°C with continuous stirring. During the process, triethanolamine was added dropwise to keep the pH of the reaction solution at 11. The addition time was 1 hour, and then the reaction was carried out at 40°C for 3 hours to obtain a modified ethylenediamine ion chelating agent.

[0025] In the composite additive, the mass ratio of the polycarboxylate water reducer to the modified ethylenediamine ion chelating agent is 1:2.

[0026] Preferably, the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material includes the following raw material components by mass percentage: 40% red mud precursor cementitious material, 43% solid waste material, 1% alkali activator, 15% sulfate activator, and 1% composite additive.

[0027] The second aspect of the present invention provides a method for preparing a supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as a raw material, comprising the following steps:

[0028] 1) Preparing a red mud precursor gelling material: mixing red mud, calcium carbonate and dihydrate gypsum, calcining at 950-1050° C. for 1-4 h, and cooling to obtain a red mud precursor gelling material;

[0029] 2) The red mud precursor gelling material is uniformly mixed with other raw material components for preparing the supersulfate-activated low-carbon gelling material to obtain the supersulfate-activated low-carbon gelling material based on alkali-containing solid waste as raw material.

[0030] The beneficial effects of the present invention are:

[0031] The present invention provides a supersulfate-activated low-carbon cementitious material based on alkaline solid waste as raw materials and a preparation method thereof. The present invention expands the application scope of the sulfate-activated low-carbon cementitious material system, making alkaline solid waste such as red mud a necessary component thereof, and can simultaneously solve the problem of shortage of high-quality auxiliary cementitious materials and the environmental problems caused by red mud storage;

[0032] The heat-activated red mud (red mud precursor gelling material) in the formula of the present invention not only provides high-activity aluminum-silica potential for the performance development of the gelling material, but also provides appropriate alkalinity to compensate for the strength decline caused by insufficient alkali in the later stage of the system, thereby promoting the improvement of the mechanical strength of the gelling material and the densification of the matrix;

[0033] The high iron and high alkali characteristics of red mud in the formula of the present invention effectively reduce the calcination temperature of calcium sulfosilicate by about 50-100°C, improve the calcinability of calcium sulfosilicate, and reduce energy consumption loss and carbon emissions during calcination; calcium sulfosilicate can regulate the concentration of alkali metal ions to compensate for the effects of excessive alkalinity in the early stage and insufficient alkalinity in the later stage on the mechanical properties of cementitious materials;

[0034] The organic composite additive C containing the homemade modified ethylenediamine ion chelating agent in the formula of the present invention has a significant effect on improving the compressive strength of the cementitious material. The modified ethylenediamine ion chelating agent can effectively chelate sodium ions in the early stage of the hydration reaction to form a stable multi-chelate structure, thereby reducing the alkalinity in the early hydration environment, which is beneficial to the early hydrolysis reaction of mineral powder and red mud and promotes the development of compressive strength.

[0035] The present invention can achieve efficient utilization of red mud, and provide theoretical support for the application of red mud and the development of sulfate-stimulated low-carbon cementitious material systems; the present invention can reduce carbon emissions in the production process of building materials; through the resource utilization of solid waste, environmental pollution is reduced and resources are saved, the development of green buildings is promoted, and it can help the transformation and upgrading of the building materials industry in an environmentally friendly and sustainable direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The compressive strength test results of the supersulfate-activated low-carbon cementitious materials of Comparative Example 1 and Example Groups 1 to 3;

[0037] Figure 2 The compressive strength test results of the supersulfate-activated low-carbon cementitious materials of Example Group 2, Example Group 4, and Example Group 5;

[0038] Figure 3 Comparison of compressive strength test results of supersulfate-activated low-carbon cementitious materials of Example Group 5 and Example Group 6. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0040] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0041] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0042] The invention provides a supersulfate activated low-carbon cementitious material based on alkali-containing solid waste as raw materials, comprising the following raw material components by mass percentage: 30-50% of red mud precursor cementitious material, 34-54% of solid waste material, 0.5-2% of alkali activator and 10-20% of sulfate activator.

[0043] In a preferred embodiment, the preparation method of the red mud precursor gelling material is: mixing red mud, calcium carbonate and dihydrate gypsum, calcining at 950-1050° C. for 1-4 hours, cooling, and obtaining the red mud precursor gelling material, wherein the mass ratio of red mud: calcium carbonate: dihydrate gypsum is 6.9-13.9:2.3:1.

[0044] After the mixture of red mud, calcium carbonate and dihydrate gypsum is calcined at high temperature, the activity of red mud can be stimulated. Generally speaking, the fired red mud precursor cementitious material contains 90-99% active red mud and 1-10% calcium sulfosilicate. The phases mainly include hematite-Fe2O3, nepheline-KNa3[AlSiO4]4 and calcium sulfosilicate. The activation temperature of red mud is 950-1050℃. The calcined red mud at this temperature has the highest aluminum active minerals. During the firing process of calcium sulfosilicate in the calcium temperature range, it is affected by the iron phase in the red mud, and the firing temperature is reduced by 50-100℃.

[0045] In a preferred embodiment, the solid waste material is blast furnace powder, wherein the contents of activated alumina and silicon oxide are not less than 35% and 15% respectively.

[0046] In a preferred embodiment, the alkali activator is at least one of commercially available silicate cement (such as P·II42.5 silicate cement), clinker, calcium hydroxide, etc.

[0047] The sulfate activator is a gypsum mineral, which can be selected from at least one of anhydrite, anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, phosphogypsum, etc., and the effective component is ≥95%.

[0048] In a preferred embodiment, the raw material components of the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material also include a composite additive with a weight percentage of 0.5-2%, and the composite additive is a mixture of a concrete early strength agent, a polycarboxylate water reducer, and an ion chelating agent;

[0049] Among them, the mass ratio of concrete early strength agent: polycarboxylate water reducer: ion chelating agent is 4:1:2;

[0050] Wherein, the concrete early strength agent is triethanolamine, and the ion chelating agent is ethylenediamine ion chelating agent.

[0051] In another preferred embodiment, the raw material components of the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw materials also include a composite additive with a mass proportion of 0.5-2%, and the composite additive is a mixture of a polycarboxylate water reducer and a modified ethylenediamine ion chelating agent, and the mass ratio of the polycarboxylate water reducer to the modified ethylenediamine ion chelating agent is 1:2;

[0052] Wherein, the modified ethylenediamine ion chelating agent is prepared by the following method:

[0053] Add 100-400g of ethylenediamine to a four-necked flask, add 7.5-30g of formaldehyde dropwise at 0°C with continuous stirring, and simultaneously add triethanolamine dropwise during the process to keep the pH of the reaction solution not less than 11. The addition time is 0.5-2h, and then react at 30-50°C for 1.5-6h to obtain a modified ethylenediamine ion chelating agent.

[0054] In a more preferred embodiment, the modified ethylenediamine ion chelating agent is prepared by the following method:

[0055] 200 g of ethylenediamine was added to a four-necked flask, and 15 g of formaldehyde was added dropwise at 0°C with continuous stirring. During the process, triethanolamine was added dropwise to keep the pH of the reaction solution at 11. The addition time was 1 hour, and then the reaction was carried out at 40°C for 3 hours to obtain a modified ethylenediamine ion chelating agent.

[0056] In the composite additive, the mass ratio of polycarboxylate water reducer to modified ethylenediamine ion chelating agent is 1:2.

[0057] Among them, since the triethanolamine added for controlling pH in the preparation process of the modified ethylenediamine ion chelating agent can also be used as a concrete early strength agent, there is no need to add a concrete early strength agent to the composite additive at this time. In this embodiment, triethanolamine can play a role in controlling pH in the process of preparing the modified ethylenediamine ion chelating agent, and can also be used as an active ingredient of the concrete early strength agent in the subsequent composite additive, which can save the production cost of the composite additive, and can make triethanolamine and ethylenediamine ion chelating agent have better uniformity, which is more conducive to their respective roles in the cementitious material.

[0058] The present invention also provides a method for preparing the supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as a raw material, comprising the following steps:

[0059] 1) Preparing a red mud precursor gelling material: mixing red mud, calcium carbonate and dihydrate gypsum, calcining at 950-1050° C. for 1-4 h, and cooling to obtain a red mud precursor gelling material;

[0060] 2) The red mud precursor gelling material is uniformly mixed with other raw material components for preparing the supersulfate-activated low-carbon gelling material to obtain a supersulfate-activated low-carbon gelling material based on alkali-containing solid waste as a raw material.

[0061] The working principle of each part in the supersulfate-activated low-carbon cementitious material system of the present invention is as follows:

[0062] (1) Thermal activation mechanism of red mud: Under high temperature, the top-joint connection of the stable silicon-oxygen tetrahedron and aluminum-oxygen octahedron structures in red mud separates, resulting in bond breakage and activation points. The inert phase decomposes to produce active silicon-aluminum substances, thus showing volcanic ash activity.

[0063] (2) Mechanism of action of calcium sulfosilicate: alkali metal ions (mainly Na + ) mainly replaces calcium ions (Ca 2+ ) in calcium sulfosilicate (C5S2$), alleviating the influence of red mud high alkalinity on the stability of early hydration products such as ettringite. At the same time, C5S2$ has a certain late hydration reaction potential, and can still slowly release Na after hydration for 28 days. + , regulate pH changes and continuously stimulate the hydration decomposition of unreacted raw materials (mainly mineral powder) to promote later strength growth.

[0064] Hydration mechanism of sulfate-activated cementitious material system: The main hydration products are trisulfur-type hydrated calcium sulfoaluminate (ettringite) and hydrated calcium silicate gel. During the hydration process, sulfate and clinker are first dissolved in the system to form OH - Ions, Ca 2+ Ions, SO4 2- Ions and a small amount of Al 3+ Ions and Si 4+ At this time, a small amount of hydrated calcium silicate gel and hydrated calcium aluminate gel will be formed, and then the hydrated calcium aluminate gel will react with the SO4 in the system. 2- The reaction forms calcium vanadate. However, due to the limited clinker, the Al in the system 3+ Ions and Si 4+ As the reaction proceeds, the substances in the system continue to dissolve, causing the system alkalinity to reach a certain level. Under the action of OH- ions, the surface structure of the slag is destroyed, causing active SiO2 and active Al2O3 to precipitate, producing more Al 3+ Ions and Si 4+ ions, thereby forming more hydrated calcium silicate gel and hydrated calcium aluminate gel, and then in SO4 2-Under the action of ions, calcium aluminate is formed.

[0065] The hydrogen atoms of the amino group in the ethylenediamine chelating agent form nitrogen-metal coordination bonds with metal ions, and the oxygen ions of the acetic acid group form oxygen-metal coordination bonds with metal ions, eventually forming a complex; triethanolamine is a surfactant that accelerates the hydration of C3A and the formation of calcium aluminate during cement hydration, promoting the development of early strength; polycarboxylate water reducer is adsorbed on the surface of cement particles, making the surface of cement particles carry a negative charge, thereby having an electrostatic repulsion effect, promoting the mutual dispersion of cement particles and releasing the encapsulated water molecules.

[0066] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0067] The main sources of raw materials are as follows:

[0068] Red mud, from an aluminum company in Shandong, with alumina content ≥20%, silica content ≥17%, alkali content ≥8%, and calcium carbonate of analytical grade CaCO 3, Dihydrate gypsum is analytically pure CaSO4·2H2O, with an effective content of ≥99%;

[0069] Mineral powder, from Jinan Luxin New Building Materials Co., Ltd., with a particle size of about 1-100 μm;

[0070] Triethanolamine was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0071] The ion chelating agent selected was ethylenediamine ion chelating agent, purchased from Jinan Delan Chemical Co., Ltd.;

[0072] Polycarboxylate water reducer is manufactured by Jiangsu Subot Company.

[0073] The alkali activator was clinker purchased from Shandong Shanshui Cement Group Co., Ltd.;

[0074] The sulfate activator is dihydrate gypsum.

[0075] 1. First, prepare three red mud precursor gelling materials: RM0, RM1, and RM2

[0076] 1. Red mud precursor gelling material RM0:

[0077] The original red mud was dried at 105°C for 48 hours, then ground in a ball mill for 45 minutes and passed through an 80-mesh screen. The red mud was then calcined at 1000°C in a muffle furnace at a heating rate of 5°C / min. After reaching the predetermined temperature, it was kept warm for 2 hours, taken out and rapidly cooled in the air to obtain RM0 at room temperature, which was then put into a sealed bag for storage.

[0078] 2. Red mud precursor gelling material RM1:

[0079] The original red mud was dried at 105°C for 48 hours, then ground in a ball mill for 45 minutes and passed through an 80-mesh sieve. Subsequently, the original red mud, calcium carbonate, and dihydrate gypsum were mixed evenly in a mass fraction ratio of 13.9:2.3:1 and placed in a muffle furnace for calcination at 1000°C with a heating rate of 5°C / min. After reaching the predetermined temperature, the mixture was kept warm for 2 hours, taken out and rapidly cooled to room temperature in the air to obtain RM1, which was then placed in a sealed bag for storage.

[0080] 3. Red mud precursor gelling material RM2:

[0081] The original red mud was dried at 105°C for 48 hours, then ground in a ball mill for 45 minutes and passed through an 80-mesh sieve. Subsequently, the original red mud, calcium carbonate, and dihydrate gypsum were mixed evenly in a mass fraction ratio of 6.9:2.3:1 and placed in a muffle furnace for calcination at 1000°C, with a heating rate of 5°C / min. After reaching the predetermined temperature, it was kept warm for 2 hours, taken out and rapidly cooled in the air, and RM2 was obtained after reaching room temperature, which was placed in a sealed bag for storage.

[0082] 2. Pre-prepare two composite additives

[0083] 1. Composite additive B

[0084] The concrete early strength agent (triethanolamine), polycarboxylate water reducer, and ion chelating agent (ethylenediamine ion chelating agent) were uniformly mixed in a mass ratio of concrete early strength agent: polycarboxylate water reducer: ion chelating agent of 4:1:2 to obtain composite additive B.

[0085] 2. Composite Additive C

[0086] (1) Preparation of modified ethylenediamine ion chelating agent:

[0087] 200 g of ethylenediamine was added to a four-necked flask, and 15 g of formaldehyde was added dropwise at 0°C with continuous stirring. During the process, triethanolamine was added dropwise to keep the pH of the reaction solution at 11. The addition time was 1 hour, and then the reaction was carried out at 40°C for 3 hours to obtain a modified ethylenediamine ion chelating agent.

[0088] (2) According to the mass ratio of polycarboxylic acid water reducer to modified ethylenediamine ion chelating agent being 1:2, the polycarboxylic acid water reducer and the modified ethylenediamine ion chelating agent are mixed evenly to obtain composite additive C.

[0089] Example Group 1

[0090] Example 1-1

[0091] RMO, mineral powder, dihydrate gypsum and clinker were dry mixed in a dry mixer for 10 minutes according to the following mass fractions: 30% red mud precursor cementitious material, 54% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 1-1, and then prepared into a mortar sample with a water-cement (cement refers to the sum of RMO, mineral powder, dihydrate gypsum and clinker, the same below) mass ratio of 0.5.

[0092] Example 1-2

[0093] RM1, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 30% red mud precursor cementitious material, 54% mineral powder, 15% dihydrate gypsum sulfate activator, and 1% clinker alkaline activator to obtain the cementitious material in Example 1-2, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0094] Examples 1-3

[0095] RM2, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 30% red mud precursor cementitious material, 54% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious materials in Examples 1-3, and then mortar samples were prepared with a water-cement ratio of 0.5.

[0096] Example Group 2

[0097] Example 2-1

[0098] RMO, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 40% red mud precursor cementitious material, 44% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 2-1, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0099] Example 2-2

[0100] RM1, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 40% red mud precursor cementitious material, 44% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 2-2, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0101] Example 2-3

[0102] RM2, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 40% red mud precursor cementitious material, 44% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 2-3, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0103] Example Group 3

[0104] Example 3-1

[0105] RMO, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 50% red mud precursor cementitious material, 34% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 3-1, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0106] Example 3-2

[0107] RM1, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 50% red mud precursor cementitious material, 34% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 3-2, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0108] Example 3-3

[0109] RM2, mineral powder, dihydrate gypsum and clinker were dry-mixed in a dry mixer for 10 minutes according to the following mass fractions: 50% red mud precursor cementitious material, 34% mineral powder, 15% dihydrate gypsum and 1% clinker to obtain the cementitious material in Example 3-3, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0110] Comparative Example 1

[0111] The mineral powder, dihydrate gypsum and clinker were prepared in a mass fraction ratio of 84% mineral powder, 15% dihydrate gypsum and 1% clinker, and dry-mixed in a dry mixer for 10 minutes to obtain sulfate cement binder, and then a mortar sample was prepared with a water-cement ratio of 0.5.

[0112] The method for preparing the mortar sample is as follows:

[0113] Mix the cementitious material and water with the following stirring procedure: slow stirring (speed: 62±5r / min) for 120s, stop for 15 seconds, and then quickly stir (speed: 125±10r / min) for 120s; then put it into a 40mm*40mm*40mm mold, vibrate it, and transfer it to the curing room (203℃, RH95%) for curing until 1 day of demolding. Continue to cure in the curing room for 3 days and 28 days, and then test the compressive strength of the sample according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021).

[0114] The above Example Group 1 to Example Group 3 ratio summary and compressive strength test results are as follows Table 1 and Figure 1 As shown:

[0115] Table 1 Ratios and compressive strength of supersulfate activated low carbon cementitious materials with different types and amounts of red mud precursors

[0116]

[0117]

[0118] According to Table 1 and Figure 1 The test results of Example 3d and 28d compressive strength are as follows Figure 1 As shown in the figure. After hydration for 3 days, the compressive strength of the supersulfate-activated low-carbon cementitious material without C5S2$ (referring to the red mud precursor cementitious material compounded with calcium carbonate and dihydrate gypsum, namely RM1 and RM2) decreased with the increase of the mineral powder replacement rate of red mud. This is because a large amount of alkali metal Na is dissolved by red mud hydrolysis. + ions, alkalinity increases, hindering the formation of ettringite and destroying the structural stability of ettringite, resulting in a decrease in early strength. The compressive strength of supersulfate-activated low-carbon cementitious materials doped with C5S2$ increases with the increase in C5S2$ doping, because Na + Replace Ca 2+ Solid solution in C5S2$ regulates the hydration alkalinity, which is beneficial to the development of early strength.

[0119] The compressive strength change trend of the supersulfate-activated low-carbon cementitious material without C5S2$ at 28 days of hydration is consistent with that at 3 days. However, the compressive strength of the supersulfate-activated low-carbon cementitious material with C5S2$ increased significantly with the increase of C5S2$ dosage. When RM1 red mud cementitious material was used, the 28d strength of each group of samples exceeded or approached the SSC strength. When RM2 cementitious material was used, the 28d strength of each group of samples increased by 6.22%-14.51% compared with the SSC strength. This is because C5S2$ began to hydrolyze slowly and continuously in the late stage of hydration, and the sodium ions dissolved in C5S2$ gradually dissolved, and the alkalinity of the environment increased, which was conducive to making up for the problem of insufficient alkali in the late stage of SSC, further promoting the hydrolysis reaction of mineral powder, and ensuring the development of strength in the later stage. In addition, when using RM1 and RM2 red mud cementitious materials, the compressive strength when red mud replaced 30% of mineral powder and replaced 40% of mineral powder was basically the same. Therefore, using RM1 cementitious material to replace 40% of mineral powder to prepare red mud-super sulfate cement can alleviate the problems of red mud accumulation and mineral powder shortage to the greatest extent and realize the resource utilization of solid waste.

[0120] Therefore, the following is based on the addition of 40% of the red mud precursor gelling material to further optimize the effect of the composite additives on the material strength.

[0121] Example Group 4

[0122] In the formulations of Examples 2-1, 2-2, and 2-3, 1 wt% of additive A (ethylenediamine ion chelating agent) was added, and the mineral powder content was correspondingly reduced to 43 wt%;

[0123] Among them, additive A was first added to the water used to prepare the mortar samples, stirred for 5 minutes to make it evenly dispersed, and then mixed with the remaining raw materials together with water to prepare mortar samples. The method was the same as that of Example 2, and samples of Example 4-1, Example 4-2, and Example 4-3 were obtained in turn.

[0124] Example Group 5

[0125] In the ratios of Examples 2-1, 2-2, and 2-3, 1% of the self-made organic composite additive B was added, and the mineral powder content was correspondingly reduced to 43wt%;

[0126] Among them, the organic composite additive B is first added to the water used to prepare the mortar samples, stirred for 5 minutes to make it evenly dispersed, and then mixed with the remaining raw materials together with water to prepare mortar samples. The method is the same as that of Example 2, and samples of Example 5-1, Example 5-2, and Example 5-3 are obtained in turn.

[0127] Example Group 6

[0128] In the ratios of Examples 2-1, 2-2, and 2-3, 1% of the self-made organic composite additive C was added, and the mineral powder content was correspondingly reduced to 43wt%;

[0129] Among them, the organic composite additive C was first added to the water used to prepare the mortar samples, stirred for 5 minutes to make it evenly dispersed, and then mixed with the remaining raw materials together with water to prepare mortar samples. The method was the same as that of Example 2, and samples of Example 6-1, Example 6-2, and Example 6-3 were obtained in turn.

[0130] The above Example Group 4 to Example Group 6 ratio summary and compressive strength test results are as follows Table 2 and Figure 2-Figure 3 As shown:

[0131] Table 2 Effects of different additives on the compressive strength of supersulfate activated low carbon cementitious materials

[0132]

[0133] According to the test results, the compressive strength of the 3d and 28d groups ( Figure 2), after hydration for 3 days, the compressive strength of Example 4-1 is only 5% higher than that of Example 2-1, while the early strength of Example 5-1 is increased by up to 85% under the action of organic solvent B. After using RM1 and RM2 red mud cementitious materials to replace RM0, the early compressive strength is significantly improved, among which the early strength of Examples 5-2 and 5-3 exceeds that of Comparative Example 1, which shows that the organic composite addition B can effectively improve the 3d compressive strength of red mud-supersulfate cement cementitious materials, making it reach or exceed the 3d compressive strength of supersulfate cement. After hydration for 28 days, the compressive strength of Example 4 is significantly improved compared with Comparative Example 1. Under the action of different red mud materials, the compressive strength is increased by 4.3%, 2.52%, and 4.11%, respectively, while the compressive strength of the sample of Example 5 containing the homemade organic solvent B is increased by 7.30%, 5.12%, and 10.40%, respectively, and at this time, the compressive strength of each group of samples reaches or exceeds the 28d compressive strength of supersulfate cement.

[0134] The compressive strength test results of Example Group 5 and Example Group 6 are as follows: Figure 3 As shown,

[0135] The effect of using organic composite additive C containing homemade modified ethylenediamine ion chelating agent on improving compressive strength is significantly higher than that of organic composite additive B. This is attributed to the fact that the homemade modified ethylenediamine ion chelating agent can effectively chelate sodium ions in the early stage of hydration reaction to form a stable multi-chelate structure, thereby reducing the alkalinity in the early hydration environment, which is beneficial to the early hydrolysis reaction of mineral powder and red mud and promotes the development of compressive strength.

[0136] In summary, the organic composite additive C added in the present invention has the effect of significantly and stably improving the early and late mechanical properties of red mud-super sulfate cement (i.e., the above-mentioned super sulfate activated low-carbon cementitious material); in the present invention, by stimulating the activity of the activated red mud cementitious material, the problem of shortage of high-quality mineral powder in the preparation process of super sulfate cement can be solved, thereby achieving the purpose of resource utilization of red mud materials.

[0137] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material, characterized in that: The invention comprises the following raw material components in percentage by mass: 30-50% of red mud precursor gelling material, 34-54% of solid waste material, 0.5-2% of alkali activator and 10-20% of sulfate activator.

2. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 1, characterized in that: The preparation method of the red mud precursor gelling material is: red mud, calcium carbonate and dihydrate gypsum are mixed, calcined at 950-1050° C. for 1-4 hours, and cooled to obtain the red mud precursor gelling material.

3. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 2, characterized in that: in, The mass ratio of red mud: calcium carbonate: dihydrate gypsum is 6.9-13.9:2.3:

1.

4. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 3, characterized in that: The preparation method of the red mud precursor gelling material is as follows: The red mud was dried at 105° C. for 48 hours, ground by a ball mill for 45 minutes, passed through an 80-mesh sieve, and then mixed evenly with calcium carbonate and dihydrate gypsum, heated to 1000° C. at a heating rate of 5° C. / min, calcined for 2 hours, and taken out to cool in air to obtain the red mud precursor gelling material; Among them, the mass ratio of red mud: calcium carbonate: dihydrate gypsum is 13.9:2.3:

1.

5. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 1, characterized in that: The solid waste material is blast furnace ore powder, the alkali activator is at least one of silicate cement, clinker, and calcium hydroxide, and the sulfate activator is at least one of hard gypsum, anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, and phosphogypsum.

6. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 1, characterized in that: The raw material components also include a composite additive with a mass percentage of 0.5-2%, wherein the composite additive is a mixture of a concrete early strength agent, a polycarboxylate water reducer, and an ion chelating agent; Among them, the mass ratio of concrete early strength agent: polycarboxylate water reducer: ion chelating agent is 4:1:2; Wherein, the concrete early strength agent is triethanolamine, and the ion chelating agent is ethylenediamine ion chelating agent.

7. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 1, characterized in that: The raw material components also include a composite additive with a mass proportion of 0.5-2%, wherein the composite additive is a mixture of a polycarboxylate water reducer and a modified ethylenediamine ion chelating agent, and the mass ratio of the polycarboxylate water reducer to the modified ethylenediamine ion chelating agent is 1:2; Wherein, the modified ethylenediamine ion chelating agent is prepared by the following method: Add 100-400g of ethylenediamine to a four-necked flask, add 7.5-30g of formaldehyde dropwise at 0°C with continuous stirring, and simultaneously add triethanolamine dropwise during the process to keep the pH of the reaction solution not less than 11. The addition time is 0.5-2h, and then react at 30-50°C for 1.5-6h to obtain a modified ethylenediamine ion chelating agent.

8. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to claim 7, characterized in that: The modified ethylenediamine ion chelating agent is prepared by the following method: 200 g of ethylenediamine was added to a four-necked flask, and 15 g of formaldehyde was added dropwise at 0°C with continuous stirring. During the process, triethanolamine was added dropwise to keep the pH of the reaction solution at 11. The addition time was 1 hour, and then the reaction was carried out at 40°C for 3 hours to obtain a modified ethylenediamine ion chelating agent. In the composite additive, the mass ratio of the polycarboxylate water reducer to the modified ethylenediamine ion chelating agent is 1:

2.

9. The supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw material according to any one of claims 6 to 8, characterized in that: The invention comprises the following raw material components in percentage by mass: 40% of red mud precursor gelling material, 43% of solid waste material, 1% of alkali activator, 15% of sulfate activator and 1% of composite additive.

10. A method for preparing a supersulfate-activated low-carbon cementitious material based on alkali-containing solid waste as raw materials according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Preparing a red mud precursor gelling material: mixing red mud, calcium carbonate and dihydrate gypsum, calcining at 950-1050° C. for 1-4 h, and cooling to obtain a red mud precursor gelling material; 2) The red mud precursor gelling material is uniformly mixed with other raw material components for preparing the supersulfate-activated low-carbon gelling material to obtain the supersulfate-activated low-carbon gelling material based on alkali-containing solid waste as raw material.

Citation Information

Patent Citations

  • Phosphorus gypsum modifying material and application thereof to road base course

    CN108275931A

  • Red mud-based cementing material as well as preparation method and application thereof

    CN115974433A

  • Admixture for red-mud-based high-sulfur-resistance cement-based material as well as preparation method and application of admixture

    CN115974447A

  • Machine-made sand tailing mud self-compacting backfill material based on phosphogypsum and preparation method and application of machine-made sand tailing mud self-compacting backfill material

    CN116177974A

  • Red mud-based low-carbon composite cement and preparation method thereof

    CN117049802A

Cited By

  • Red mud-based salt-excited cementing material based on acidification-thermal activation as well as preparation method and application of red mud-based salt-excited cementing material

    CN119797787A